NASKAH PERUKUNAN BATU CANGKU: PERAN DAKWAH TUAN GURU TERHADAP PERKEMBANGAN BUDAYA LITERASI MASYARAKAT MUSLIM-SASAK - Hamzani, Yusri (UIN Mataram, 2018)
This paper discusses the diversity of Sasak villagers at Batu Cangku, Sapit village, Suela subdistrict, East Lombok, West Nusa Tenggara in the past. This paper concerns on three major issues; (1) The history of the diversity of Sasak villagers in the past, (2) The role of Islamic teachers to transform the diversity, (3) The frst Mazhab adopted by the villagers after the transformation from Islam Wetu Telu to Islam Waktu Lima. These issues were analyzed with min alnÄá¹£ ilÄ al-wÄqiâ€™. Regarding to the history of the diversity of Sasak villagers, the present researcher found that the transformation occured in their faith;started from Animism-Dinamism, HinduBuddha, Boda Sasak-Islam. In applying Islamic thought, they were divided into two different communities; Islam Wetu Telu and Islam Waktu Lima. The frst community was closer to Islam Abangan in Java, while the second community was the same as Islam as general. In addition, in relation to Islamic teachers, they were as the agents of change of this transformation. Meanwhile, in term of the thought adopted, the majority of Islamic teachers taught Mazhab SyÄfâ€™i. As a result, The villagers, the frst generation of Islam Waktu Lima, practiced this Mazhab for their worship. The data were found in a manuscript of Islam Waktu Lima as their guidance for daily worship.